Green manure - Paparella, Antonio; Petsakos, Athanasios; Davis, Kristin E.; Song, Chun (International Food Policy Research Institute, 2025)
Soil management is a critical aspect of crop production for its impact on environmental and economic sustainability. Ordinarily, in annual cropping systems, land lays fallow in the period that follows the harvest of one crop and precedes the sowing of the next. This period of non-cultivation helps reconstitute the soil fertility and water reserves [1], [2]. However, improperly maintaining the land fallow is shown to deplete soil quality and harm the environment. Without vegetation cover, the soil is more exposed to erosion [3], surface runoff [4], and degradation of its organic content [4]. Erosion and surface runoff not only reduce soil fertility, leading to an inefficient use of resources [3], but also pose a potential threat of freshwater contamination with nitrates and other agricultural by-products [5]. The degradation of soil organic matter has severe impacts when not reconstituted and preserved. The soil's capacity to hold water [3] and nutrients decreases, making control of those critical inputs complex for farmers. Climate regulation is also affected: soil organic matter stores carbon within the soil ecosystem, but its degradation releases it into the atmosphere, exacerbating greenhouse gas levels [6]